تأثير التنويع في محفظة الابتكارات التسويقية على الحصة السوقية (دراسة مسحية على القطاع المصرفي الخاص في سورية) - قاسم سامر (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تعتبر عملية تحقيق التوازن في محفظة الابتكارات التسويقية أحد متطلبات نجاح الابتكار التسويقي في المنظمة والتي بدورها تنعكس إيجاباً على الأداء من خلال توزيع المخاطر وتخفيضها, وتبرز أهميتها في ظل البيئة الاقتصادية الحديثة التي تتسم بالتغير المستمر والمخاطر المتجددة. يهدف البحث إلى دراسة استراتيجيات التنويع في محفظة الابتكارات التسويقية في المصارف الخاصة السورية وتأثير ذلك على الحصة السوقية. ولتحقيق ذلك استخدم الباحث مؤشر انتروبي ENTROPY لقياس درجة التنوع في محفظة الابتكارات التسويقية واستخدام التحليل العنقودي الهرمي لتصنيف المجموعات وفقاً لمتغيري التنوع والحصة السوقية للمصارف المدروسة بواسطة الرزمة الإحصائية للعلوم الاجتماعية SPSS V(23) ليتوصل الباحث إلى عدة نتائج أهمها: يوجد اختلاف في استراتيجيات التنويع في محفظة الابتكارات التسويقية الخاصة بالمصارف المدروسة, وارتفاع قيمة مؤشر التنوع للمصارف التي حققت حصة سوقية مرتفعة وانخفاضه لأغلب المصارف التي حصصها السوقية منخفضة. وبناء عليه, اقترح الباحث تطوير نماذج أعمال المصارف بهدف زيادة قيمة الخدمات المصرفية المبتكرة, وتحقيق التمايز في استراتيجيات التنويع المتبعة لتقليل المخاطر المختلفة. The process of achieving balance in the portfolio of marketing innovations is one of successful marketing innovation’s requirements in the Organization, which in turn reflects positively on the performance through distributing risks and reducing it, highlighting its importance inside modern economic environment witch characterizes by constant change and the renewable risks. The research aims to study the strategies of diversification in a portfolio of marketing innovations in the Syrian private banks and its impact to market share. To achieve this, the researcher used the Entropy index to measure the degree of diversity in the portfolio of marketing innovations. and use the hierarchical cluster analysis to categorize groups according to the variables of diversity and market share of the studied banks using Statistical Package for Social Sciences SPSS V (23) to reach Researcher to the following findings: There is a difference in the diversification strategies inside portfolio of marketing innovations for studied banks. And banks which achieve high value of the variety index are whose have high market share While the value of index was law for most of banks which their market shares are low, and therefore, researcher suggested that banks have to Develop their Business models in order to increase the value of innovative banking services and achieve differentiation in the followed diversification strategies to reduce the various risks.